2013
DOI: 10.1073/pnas.1315887110
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of Bacillus subtilis GabR, an autorepressor and transcriptional activator of gabT

Abstract: Significance GabR is a member of the MocR/GabR subfamily of the GntR family of bacterial transcription regulators. It regulates the metabolism of γ-aminobutyric acid, an important nitrogen and carbon source in many bacteria. The crystal structures reported here show that this protein has evolved from the fusion of a type I aminotransferase and a winged helix-turn-helix DNA-binding protein to form a chimeric protein that adopts a dimeric head-to-tail configuration. The pyridoxal 5′-phosphate–binding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
143
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(157 citation statements)
references
References 20 publications
13
143
1
Order By: Relevance
“…2) sequences, used as seed for model building, revealed that they sharẽ 36% sequence identity: this result is in line with the previously reported average sequence conservation within Firmicutes MocRs [13]. The alignment shows the conservation of the DNA-binding domain sequence and, in particular, of residues Arg43, Ser52 and Lys75, which is predicted to constitute the major DNA-binding surface in GabR [18]. Also, the key PLP interacting residues Asp276 and Lys309 (numbering referred to bcPdxR sequence), which hydrogen-bonds to the nitrogen atom of the pyridine ring and reacts with the cofactor aldehyde group at the 5 0 position of PLP forming a Schiff-base, respectively, are conserved.…”
Section: B Clausii Pdxr Activates Transcription Of the Pdxst Operonsupporting
confidence: 87%
“…2) sequences, used as seed for model building, revealed that they sharẽ 36% sequence identity: this result is in line with the previously reported average sequence conservation within Firmicutes MocRs [13]. The alignment shows the conservation of the DNA-binding domain sequence and, in particular, of residues Arg43, Ser52 and Lys75, which is predicted to constitute the major DNA-binding surface in GabR [18]. Also, the key PLP interacting residues Asp276 and Lys309 (numbering referred to bcPdxR sequence), which hydrogen-bonds to the nitrogen atom of the pyridine ring and reacts with the cofactor aldehyde group at the 5 0 position of PLP forming a Schiff-base, respectively, are conserved.…”
Section: B Clausii Pdxr Activates Transcription Of the Pdxst Operonsupporting
confidence: 87%
“…In addition, members of the MocR family have a highly conserved aspartate (class I) aminotransferase domain at their C terminus, which can bind pyridoxal 5=-phosphate (PLP) as a cofactor (3,5,13,14). PLP, alone or with other small molecules, proved to modulate the DNA-binding activities of MocR family regulators (5,(13)(14)(15)(16). Since the putative PLP-binding site is highly conserved in EhuR (data not shown), we analyzed EhuR-mediated mobility shifts in the presence of PLP as well as ectoine, DABA (a catabolic end product), and aspartate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7). No significant enzyme activity has been detected in GabR (Belitsky, 2004) although the protein is able to bind GABA (Edayathumangalam et al, 2013). Second, proteins belonging to clade 1 display a surface patch (positions 362-375) rich of basic residues localized on an exposed a-helix (Edayathumangalam et al, 2013) which may suggests the presence of a DNA or protein interaction site (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few members of the MocR family have been structurally and functionally characterized: for example, GabR that regulates the utilization of g-aminobutyric acid (GABA) in B. subtilis (Belitsky, 2004) and PdxR from Listeria monocytogenes and Corynebacterium glutamicum, involved in the regulation of PLP biosynthesis (Belitsky, 2014;Jochmann et al, 2011). Recently, the crystallographic structure of the GabR protein, deposited in the Protein Data Bank (PDB) with the codes 4MGR, 4N0B, and 4TV7 (Edayathumangalam et al, 2013;Okuda et al, 2015), confirmed the presence of a fold type-I domain at the C-terminus of the regulator and opened new perspectives in deciphering the mechanism of action of MocRs. GabR is a domain swap homodimer in which the HTH domain of one subunit interacts with the PLP-binding domain of the other subunit; this is possible thanks to a very long linker that connects the two domains.…”
Section: Introductionmentioning
confidence: 99%